Bioinspired Soft Robotic Fish for Wireless Underwater Control of Gliding Locomotion. (22nd May 2022) - Lee, Jinwoo; Yoon, Yeosang; Park, Huijae; Choi, Joonhwa; Jung, Yeongju; Ko, Seung Hwan; Yeo, Woon-Hong
Abstract : Animal locomotion offers valuable references as it is a critical component of survival as animals adapting to a specific environment. Especially, underwater locomotion poses a challenge because water exerts a high antagonistic drag force against the direction of progress. However, marine vertebrates usually use much lower aerobic energy for locomotion than aerial or terrestrial vertebrates due to their unique intermittent gliding locomotion. None of the prior works demonstrate the locomotive strategies of marine vertebrates. Herein, an untethered soft robotic fish capable of reconstructing the marine vertebrates' effective locomotion and traveling underwater by controlling localized buoyancy with thermoelectric pneumatic actuators is introduced. The actuators enable both heating and cooling to control a localized buoyancy while providing a substantial driving force to the system. Besides mimicking the locomotion, the bidirectional communication system enables the untethered delivery of commands to the underwater subject and real‐time acquisition of the robotic fish's physical information. Underwater imaging validates the fish's practical use as a drone, allowing for inspecting the aquatic environment that is not easily accessible to humans. Future work studies the operation of the robotic fish as a collective swarm to examine a broader range of the underwater area and conduct various strategic missions. Abstract : Marine vertebrates employ the intermittent gliding locomotion to minimize the energy for underwater environment. Inspired by marine vertebrates, this work introduces a soft, wireless fish robot that replicates the intermittent gliding and moves in the underwater space by soft thermoelectric pneumatic actuators.